Disclosure Of Community Welfare: Implications Of Super Premium Tourism Program Implementation: (Studies of the Department of Tourism, Creative Economy and Culture of West Manggarai) - Febronia Hersi Batul; Ikhsan Budi Riharjo; Fidiana (Lead Journal of Economy and Administration, 2023)
This study aimed to find out whether public wealth indicated the implementation of Labuan Bajo, the super-premium tourism program, in the Manggarai Barat sub-district. Moreover, the data were both primary in the form of interviews and secondary in the form of documents. The study was descriptive- qualitative with a case-study approach. Furthermore, the informants were the head of the office, the head of the creative cluster, and also making its analysis. As a result, the implementation of the super-premium tourism object affected the Local Owned-source Revenue, improved natural resources, infrastructure, and the disclosure of public wealth. Likewise, the implementation of Labuan Bajo had been well-applied as the public revenue level was inclined, education access was easily obtained, and better quality of public health.